Risk of liver‐related events by age and diabetes duration in patients with diabetes and nonalcoholic fatty liver disease. Issue 5 (7th April 2022) - Zhang, Xinrong; Wong, Grace Lai‐Hung; Yip, Terry Cheuk‐Fung; Cheung, Johnny T. K.; Tse, Yee‐Kit; Hui, Vicki Wing‐Ki; Lin, Huapeng; Lai, Jimmy Che‐To; Chan, Henry Lik‐Yuen; Kong, Alice Pik‐Shan; Wong, Vincent Wai‐Sun
Abstract: Background and Aims: Several guidelines recommend screening for NAFLD in patients with type 2 diabetes (T2D). We aimed to determine if there is a threshold of age and duration of T2D for liver‐related event development to guide screening strategies. Approach and Results: We conducted a territory‐wide retrospective cohort study of adult patients with NAFLD and T2D diagnosed between 2000 and 2014 in Hong Kong to allow for at least 5 years of follow‐up. The primary endpoint was liver‐related events, defined as a composite of HCC and cirrhotic complications. This study included 7028 patients with NAFLD with T2D (mean age, 56.1 ± 13.3 years; 3363 male [47.9%]). During a follow‐up of 77, 308 person‐years, there was a threshold effect with 1.1%, 4.9%, and 94.0% of patients developing liver‐related events at the age of <40, 40–50, and ≥50 years, respectively. Similarly, 3.1%, 5.1%, and 91.8% of patients developed cirrhosis at the age of <40, 40–50, and ≥50 years, respectively. In contrast, liver‐related events increased linearly with diabetes duration, with no difference in the annual incidence rate between the first 10 years of T2D diagnosis and subsequent years (0.06% vs. 0.10%; p = 0.136). On multivariable analysis, baseline age ≥50 years (adjusted HR [aHR] 2.01) and cirrhosis (aHR 3.12) were the strongest risk factors associated with liver‐related events. Substitution of cirrhosis with the aspartate aminotransferase‐to‐platelet ratio index or the Fibrosis‐4 index yielded similar results. Conclusions: Age rather than duration of T2D predicts liver‐related events in patients with NAFLD and T2D. It is reasonable to screen patients with NAFLD and T2D for advanced liver disease starting at 50 years of age. Abstract : Diabetes is an important risk factor for nonalcoholic fatty liver disease (NAFLD) and its severity. However, it is difficult to screen every diabetic patient for NAFLD because of the large number of patients. In a study of 7028 patients with NAFLD and type 2 diabetes from Hong Kong, we showed that the vast majority of patients developed liver‐related complications after the age of 50 years. In contrast, liver‐related events increased linearly with the duration of diabetes with no threshold effect. Our study suggests that screening for liver disease should be based on age instead of the duration of diabetes.